Network Analysis of Food Security Policy in Majalengka Regency - Willya Achmad (Jurnal Sosial Sains dan Komunikasi, 2023)
Food security is a crucial issue in the development of a region that affects people's welfare. Majalengka Regency has great agricultural potential, however, its vulnerability to climate change and fluctuations in food commodity prices emphasizes the importance of analyzing the policy framework related to food security. This research aims to explain the structure of the food security policy implementation network in Majalengka Regency. This research uses a qualitative approach. Data collection techniques are in-depth interviews, documentation and observation. Data were analyzed using data reduction techniques, data presentation, drawing conclusions and verification. The research results show that the implementation of food security policies in Majalengka Regency through mutual adjustment type coordination illustrates the importance of cooperation between various entities, including government, non-government and community-based organizations. Even though there are challenges in the availability and quality of information that differ between actors, the cross-departmental meeting initiated by the Majalengka Regency DKPP succeeded in creating an adequate adjustment process to ensure the achievement of food security policy goals. This emphasizes the need for structured collaboration and synergy between various related parties in order to realize sustainable and effective food security for local communities.